2(8b+2)-1+4g-(2-5g)=

Simple and best practice solution for 2(8b+2)-1+4g-(2-5g)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(8b+2)-1+4g-(2-5g)= equation:


Simplifying
2(8b + 2) + -1 + 4g + -1(2 + -5g) = 0

Reorder the terms:
2(2 + 8b) + -1 + 4g + -1(2 + -5g) = 0
(2 * 2 + 8b * 2) + -1 + 4g + -1(2 + -5g) = 0
(4 + 16b) + -1 + 4g + -1(2 + -5g) = 0
4 + 16b + -1 + 4g + (2 * -1 + -5g * -1) = 0
4 + 16b + -1 + 4g + (-2 + 5g) = 0

Reorder the terms:
4 + -1 + -2 + 16b + 4g + 5g = 0

Combine like terms: 4 + -1 = 3
3 + -2 + 16b + 4g + 5g = 0

Combine like terms: 3 + -2 = 1
1 + 16b + 4g + 5g = 0

Combine like terms: 4g + 5g = 9g
1 + 16b + 9g = 0

Solving
1 + 16b + 9g = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + 16b + -1 + 9g = 0 + -1

Reorder the terms:
1 + -1 + 16b + 9g = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 16b + 9g = 0 + -1
16b + 9g = 0 + -1

Combine like terms: 0 + -1 = -1
16b + 9g = -1

Add '-9g' to each side of the equation.
16b + 9g + -9g = -1 + -9g

Combine like terms: 9g + -9g = 0
16b + 0 = -1 + -9g
16b = -1 + -9g

Divide each side by '16'.
b = -0.0625 + -0.5625g

Simplifying
b = -0.0625 + -0.5625g

See similar equations:

| -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) | | 6x=6(x+5)+6 | | 4x-8=4x+9 | | 4=-2x+36 | | 7.4x-1.1=13.7 | | 3x^2+9x-44=0 | | 4(x+6)=21 | | 8(6)+9y=36 |

Equations solver categories